Pengaruh Metode Inkuiri Learning Mat Pelajaran Al-Qur’an Hadits Terhadap Kemampuan Berpikir Kritis Kelas IX Di MTs Bustanul Arifin - Istiqorotul Nur Imami Sayid; Khusnan, Achmad; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2024)
The focus of this study is on the ninth-grade students at MTs, with the main goal of showcasing how inquiry-based learning approaches are applied in teaching Qur'an and Hadith. Furthermore, the research aims to explore the development of students' critical thinking abilities during the learning process. Another key aim is to evaluate how inquiry-based learning influences the teaching of Qur'an and Hadith at MTs Bustanul Arifin, which is situated in Kebondalem Menganti, Gresik. The study adopts a descriptive quantitative approach, involving the entire population of 70 ninth-grade students. A saturation sampling technique is employed, ensuring that the sample size remains at 70 students. Data collection is conducted through various methods, including observation, questionnaires, and documentation. The data analysis employs simple linear regression, utilizing SPSS software version 23. The results highlight a noteworthy impact of the inquiry-based learning approach on the critical thinking skills of ninth- grade students at MTs Bustanul Arifin, Kebondalem Menganti, Gresik. This conclusion is drawn from a t-value of 8.685, which exceeds the threshold t-value of 1.668 at a 5% significance level (0.05). As the t-value (8.685) is higher than the critical value (1.668), the null hypothesis (H0) is rejected, while the alternative hypothesis (Ha) is accepted. This confirms that inquiry-based learning contributes significantly to the improvement of students' critical thinking abilities.